Analysis of the energy spectra of ground states of deformed nuclei in the rare-earth region - Okhunov, Abdurahim; Turaeva, Gulyuz; Kassim, Abu Hasan; Khandaker, Mayeen Uddin; Rosly, Noora (IOP Publishing, 2015)
The 62Sm, 64Gd, 66Dy, 70Yb, 72Hf and 74W nuclei are classified as deformed nuclei. Low-lying bands are one of the most fundamental excitation modes in the energy spectra of deformed nuclei. In this paper a theoretical analysis of the experimental data within the phenomenological model is presented. The energy spectra of ground states are calculated. It is found that the low-lying spectra of ground band states are in good agreement with the experimental data.